2008
DOI: 10.4489/myco.2008.36.1.028
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Culture Conditions for Mycelial Growth of Korean Wild Strains inGanoderma lucidum

Abstract: Ganoderma lucidum (Fr.) Karst (Polyporaceae), belonging to basidiomycota, is one of the most famous medicinal mushrooms. This study was carried out to investigate favorable mycelial growth conditions, such as pH, temperature, growth media, carbon sources and nitrogen sources of Korean strains in G. lucidum. The most suitable temperature for the mycelial growth was obtained at 30℃. In general, optimal temperature range for the mycelial growth was found at 25~30℃. This Mushroom has a broad pH range (5~9) for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
(24 reference statements)
8
30
1
1
Order By: Relevance
“…Hexose stimulated cellulase production in C. occidentalis (0.60 unit/mL), Pogonomyces hydnoides (0.25 units/mL), N. hygrophanus (0.24 unit/mL) and Podoscyha bolleana (0.22 units/mL). Similar utilization of glucose was reported by Jonathan [2] for different Nigerian higher fungi, Jayasinghe et al [27] and Adejoye and Fasidi [26] reported glucose as the most stimulatory carbohydrate source for mycelial production in G. lucidum and S. commune. Glucose utilization for enzyme production may be attributed to the ease by which this sugar is oxidized to produce cellular energy.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Hexose stimulated cellulase production in C. occidentalis (0.60 unit/mL), Pogonomyces hydnoides (0.25 units/mL), N. hygrophanus (0.24 unit/mL) and Podoscyha bolleana (0.22 units/mL). Similar utilization of glucose was reported by Jonathan [2] for different Nigerian higher fungi, Jayasinghe et al [27] and Adejoye and Fasidi [26] reported glucose as the most stimulatory carbohydrate source for mycelial production in G. lucidum and S. commune. Glucose utilization for enzyme production may be attributed to the ease by which this sugar is oxidized to produce cellular energy.…”
Section: Resultssupporting
confidence: 85%
“…Conversely, little or no amylase and cellulase activity were observed at 35 and 40 o C. Enzyme activity is reduced at high temperatures [24]. Table 2 results are similar to those obtained by Jayasinghe et al [27], who suggested that 25~30 o C was a favourable temperature for mycelial growth of a wild strain of Ganoderma lucidum from Korea. Similarly, Adejoye and Fasidi [26] reported that 28 o C was the optimum temperature for producing laccase in S. commune.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Other sugar sources, in particular, sorbitol, mannitol, fructose, sucrose, dextrin, and mannose (in descending order in terms of growth rate), were reported to result in better growth for G. applanatum compared to glucose (Jo et al 2009). In a separate study, dextrin was the most preferred source for G. lucidum growth, followed by galactose and fructose, but glucose also resulted in the slowest growth (Jayasinghe et al 2008). Information on the responses of five Ganoderma isolates to three different simple sugars was used for cluster analysis.
10.1080/21501203.2015.1137985-F0001Figure 1.Contour plots of radial mycelial growth (mm/day) for G. australe G30 (a), (b); Ganoderma sp.
…”
Section: Resultsmentioning
confidence: 99%
“…Pat. grew better at around pH 5 (acidic) (Nawawi and Ho 1990; Jayasinghe et al 2008; Jeong et al 2009; Kapoor and Sharma 2014). In addition, oil palm extracts were reported to have pH 5 (unpublished data).…”
Section: Introductionmentioning
confidence: 99%